Neonatal Onset Distal Renal Tubular Acidosis: Description of Two Novel Variants on the ATP6V0A4 Gene and Review of the Literature on Associated Extrarenal Manifestations - Antoniadi, Marita; Lambrou, Dimitra; Mylona, Fani; Florentin, Lina; Bili, Chrysanthi; Stefanidis, Constantinos J.; Kostaridou, Stavroula (Journal of Pediatric Genetics, 2023)
Distal renal tubular acidosis (dRTA) is an extremely rare disease that affects the distal tubule's ability to excrete proton cations, acidify urine, and maintain the acid–base balance. The clinical presentation of dRTA typically includes normal anion gap metabolic acidosis with decreased serum bicarbonate levels, hypokalemia, hypercalcemia, nephrocalcinosis, and alkaline urine. Hereditary causes of dRTA include pathogenic variants in ATP6V1B1, ATP6V0A4, SLC4A1, FOXI1, and WDR72 genes, which encode different transmembrane proteins on the apical surface of type A intercalated cells in the distal tubule. Variants in these genes lead to various defects in the function of the encoded proteins and can also account for extrarenal manifestations of dRTA due to the expression of these proteins in other organs, such as the stria vascularis of the inner ear. However, the literature on extrarenal manifestations, associated renal complications of hereditary dRTA, and appropriate investigations, and follow-up for patients with dRTA is scarce. In this article, we present a challenging case of neonatal-onset dRTA and contribute two novel variants of the ATP6V0A4 gene and a novel phenotype associated with a pathogenic variant on ATP6V0A4 to the scientific community. We also review the existing literature on hereditary causes of dRTA, with emphasis on associated renal and extrarenal complications.
Keywords: dRTA; neonatal; ATP6V0A4; hypokalemia; failure to thrive